PREPROCESSING PADA SEGMENTASI CITRA PARU-PARU DAN JANTUNG MENGGUNAKAN ANISOTROPIC DIFFUSION FILTER - Widyantara, I Made Oka; Kusuma, A. T. A Prawira; Wirastuti, N. M. A. E. Dewi (Majalah Ilmiah Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2015.v14i02p02, 2015)
This paper propose a preprocessing techniques in lung segmentation scheme using Anisotropic Diffusion filters. The aim is to improve the accuracy, sensitivity and specificity results of segmentation. This method was chosen because it has the ability to detect the edge, namely in doing smoothing, this method can obscure noise, while maintaining the edges of objects in the image. Characteristics such as this is needed to process medical image filter, where the boundary between the organ and the background is not so clear. The segmentation process is done by K-means Clustering and Active Contour to segment the lungs. Segmentation results were validated using the Receiver Operating Characteristic (ROC) showed an increased accuracy, sensitivity and specificity, when compared with the results of segmentation in the previous paper, in which the preprocessing method used is Gaussian Lowpass filter.
Keywords: Preprocessing, anisotropic diffusion filter, segmentasi, medical imaging, clustering, x-ray thorax